Post-Consumer Recycled Aluminium for Aerosol Valves - Gausmann, Christine (Digital Repository of Theses, 2026)
This study examines the environmental and economic feasibility of using 100% post-consumer recycled (PCR) aluminium in aerosol valve mounting cups. While aluminium is theoretically infinitely recyclable, challenges arise in meeting the strict alloy and surface-quality requirements for these niche applications. (Stacey 2015). The research compares two low-carbon strategies: sourcing primary aluminium from energy-efficient producers and increasing the use of PCR aluminium. Findings show that, despite its environmental appeal, PCR aluminium faces significant constraints, including limited availability of alloy-compatible scrap and inconsistent aesthetic properties.(European Aluminium, 2025c) Drawing on industry reports and literature, the study highlights that current recycling systems are insufficient to deliver the required purity and volume. Although the use of PCR aluminium could reduce carbon emissions, practical limitations hinder its broad adoption in specialised packaging components. Further research and industry collaboration are needed to close the gap between sustainability goals and technical feasibility in these markets. (Reinhardt, 2023) This dissertation investigates the environmental benefits of using 100% post-consumer recycled (PCR) aluminium in the production of aerosol valve mounting. Using a causal-explanatory research design, the study examines the impact of increasing PCR content on the carbon footprint of aluminium packaging components and assesses the technical feasibility of replacing traditional alloys (e.g., 5754) with more widely available PCR-compatible alternatives, such as aluminium grade 3104. (Aditya Birla Novelis, 2022) Using a deductive, empirical approach, the study tests the hypothesis that both first-class primary aluminium (sourced from low-carbon smelters) and 100% PCR aluminium can significantly reduce greenhouse gas emissions. Primary and secondary data are collected from aluminium producers, packaging suppliers, and industry publications. (Karbach-Parr, 2019) Initial findings confirm that while PCR aluminium lowers CO₂ emissions (0.5–0.6 t CO₂/t Al vs. ~10 t for primary), alloy purity and scrap availability remain significant constraints. The research proposes 3104 as a viable alternative to enable broader adoption of PCR aluminium and establishes a benchmark for sustainable innovation in niche aluminium packaging segments.